"It's ignorant stereotypes": Key stakeholder perspectives on stereotypes associated with fetal alcohol spectrum disorder, alcohol, and pregnancy. Issue 1 (2nd January 2022) - Aspler, John; Bogossian, Aline; Racine, Eric
ABSTRACT: Background: People with fetal alcohol spectrum disorder (FASD) and women who drink alcohol while pregnant can experience stigma, possibly exacerbated by stereotyped media portrayals. Method: To understand experiences of FASD stakeholders and reactions to news coverage, we conducted twelve focus groups across three categories: (1) people with FASD; (2) caregivers; and (3) professionals. Themes were identified using framework analysis . Results: We identified stereotypes about: (1) FASD (e.g., negative life trajectories); (2) alcohol and pregnancy (e.g., bad mothers); and (3) non-biological caregivers. Participants identified potential effects of FASD stereotypes (e.g., self-fulfilling prophecies) and alcohol and pregnancy stereotypes (e.g., exacerbating difficult decisions about disclosing a child's adoptive status). Conclusions: Our results align with research about difficult experiences of FASD stakeholders. However, while Canadian news analyses found people with FASD portrayed as criminals, our participants identified mostly non-crime stereotypes. Participants also sometimes shifted the burden of motherhood stereotypes from low-income to higher-income women.